PENENTUAN SUMBER GEMPA LOKAL BERDASARKAN WAKTU TIBA GELOMBANG P DAN S: STUDI KASUS LENGAN UTARA PULAU SULAWESI - A.M. Miftahul Huda; Ain Sahara (Sekolah Tinggi Teknologi MIGAS, 2021)
Determination of the source of the earthquake has been carried out in the north arm of Sulawesi. The earthquakes analyzed were a local earthquake with a magnitude of more than 5 M. The source of the earthquake is the main variable in earthquake disaster mitigation. Determining the source of the earthquake using the arrival time of the P/S wave. The arrival times of the P/S waves were validated with a Wadati’s chart to test the convergence of the data. Determination of the source of the earthquake was analyzed using HYPOINVERSE. The source of the earthquake obtained has variations in depth and position. Comparison with the catalog shows a significant difference.